Implementación de un manual de buenas prácticas de manufactura para la mejora de la calidad del snack de Sacha-Inchi en “FOCAZNOM” - Zambrano Loor, Jacqueline Elizabeth (2023)
The objective of the research was to implement a Good Manufacturing Practices Manual (GMP) in the FOCAZNOM organization to improve the quality of the Sacha-Inchi snack. For this purpose, an interview and checklist were used in accordance with resolution ARCSA-067-2015-GG. Interviews were conducted with the legal representative and operators, who indicated that the microenterprise still did not comply with all the required safety standards, and finally, bromatological and microbiological analyses (peroxide index, mesophilic aerobes, mold count, Escherichia coli) were performed on the Sacha-Inchi snack under INEN 2570, which showed an impermissible result. In summary, in this phase an average of 36% compliance was obtained in all aspects. After the diagnosis, a plan of activities was drawn up in accordance with the ARCSA to correct the aspects that were lacking in the microenterprise and thus take corrective and preventive measures for snack production. Subsequently, it was verified with the same diagnostic instruments, where 83% compliance was achieved. This confirms that through the implementation of the GMP manual, the quality of the Sacha-Inchi snack was improved in the microenterprise, ensuring food safety.